The effects of lower-limb wearable resistance on sprint performance in high school American football athletes: A nine-week training study. Issue 5 (October 2021) - Feser, Erin H; Korfist, Christian; Lindley, Kyle; Bezodis, Neil E; Clark, Kenneth; Cronin, John
Time constraints often result in the challenge to fit desired programming into training time allotments. Wearable resistance (WR) may be an option to optimise the training content in function of constrained training time. The purpose of this study was to determine the effects of a lower-limb WR sprint running training intervention on athlete speed capabilities following a nine-week off-season, low volume training period within a sample of American football high school athletes. Nineteen athletes completed pre- and post-intervention testing of two maximal effort 30 m sprints. Horizontal force-velocity mechanical profiling variables, sprint times, and maximal velocity were calculated from sprint running velocity data collected by a radar device. The athletes completed seventeen dedicated sprint training sessions during the off-season. The intervention (WR) group completed the sessions with 1% body mass load attached to the shanks (i.e. 0.50% body mass load on each limb). The control group completed the same training sessions unloaded. Post-intervention, no statistically significant between group differences were observed ( p > 0.05). However, athletes in both groups experienced increases in velocity measures following the sprint training. The greater adjusted mean theoretical maximal velocity scores ( p > 0.05; ES = 0.30) found for the WR group compared to the control group at post-intervention may suggest that WR amplifies the nuances of the training protocol itself. Coaches can consider using lower-limb WR training to increase in-session workloads during periods of low volume training but more research is needed to better understand to what extent WR training might provide an added value to optimise both the training content and planning, as well as the athlete's training response in order to improve sprint running performance.